In situ 2D-extraction of DNA wheels by 3D through-solution transport. Issue 48 (19th November 2015) - Yonamine, Yusuke; Cervantes-Salguero, Keitel; Nakanishi, Waka; Kawamata, Ibuki; Minami, Kosuke; Komatsu, Hirokazu; Murata, Satoshi; Hill, Jonathan P.; Ariga, Katsuhiko
Abstract : Nanowheel that consist of self-assembly of DNA tiles, first immobilized on hydrophilic surface, traversed to hydrophobic surface by complexation with cationic lipid. Abstract : Controlled transfer of DNA nanowheels from a hydrophilic to a hydrophobic surface was achieved by complexation of the nanowheels with a cationic lipid (2C12 N + ). 2D surface-assisted extraction, '2D-extraction', enabled structure-persistent transfer of DNA wheels, which could not be achieved by simple drop-casting.